Penerapan Take and Give untuk Meningkatkan Kemampuan Kerjasama Siswa Pada Pembelajaran Bahasa Kelas V - Halik, Abdul; Usman; Ilham, Muh. Iswar (STKIP Andi Matappa Pangkep, 2024)
This study was motivated by the low cooperation of class V UPTD SD Negeri 145 Barru students. The type of research used in this research is Classroom Action Research (PTK) using a qualitative approach. The subjects of this study were teachers and class V students as many as 20 students consisting of 8 boys and 12 girls. Data were obtained through observation and documentation techniques, then the data analysis techniques used were data condensation, data presentation, and conclusion drawing. This research consisted of 2 cycles. Each cycle includes planning, implementation, observation and reflection stages. Based on the research data from cycle I, it was found that teacher activities were in the sufficient category (C), student activities were in the sufficient category (C), and student cooperation was in the sufficient category (C). The learning results of cycle II show that teacher activities are in the good category (B), student activities are in the good category (B), and student cooperation is in the very good category. So it can be concluded that the application of the Take and Give learning model can improve cooperation in the learning process of students in Indonesian language subjects in class V UPTD SD Negeri 145 Barru.